A New Risk Index Combining d-Dimer, Fibrinogen, HE4, and CA199 Differentiates Suspecting Endometrial Cancer From Patients With Abnormal Vaginal Bleeding or Discharge. (11th March 2020) - Ge, Lili; Liu, Guangquan; Hu, Kai; Huang, Ke; zhang, Mi; Zhou, Juan; Teng, Fang; Cao, Jian; Dai, Chencheng; Jia, Xuemei
Purpose: To establish an efficient new risk index for screening patients with endometrial cancer from patients with abnormal vaginal bleeding or discharge. Method: A total of 254 patients with abnormal vaginal bleeding or discharge were included in this study. Several candidate markers, including HE4, CA125, CA199, CA153, AFP, CEA, d -dimer, and fibrinogen, were employed. A new risk index for endometrial cancer screening was established by binary logistic regression. The diagnostic value of the candidate markers and the new risk index were assessed by a receiver operating characteristic curve, sensitivity, and specificity. Results: The most valuable diagnostic indicator for endometrial cancer was HE4, followed byd -dimer and then fibrinogen (area under the receiver operating characteristic curve: HE4 = 0.794, d -dimer = 0.717, fibrinogen = 0.690). The new risk index was superior to a single application of markers and a widely used combination (HE4 and CA125). At the ideal cutoff level, the sensitivity and specificity were 91.34% and 70.08%, respectively. In addition, only patients without organic disease served as controls, which further increase its performance (area under the receiver operating characteristic curve = 0.932, sensitivity = 94.49%, and specificity = 77.42%). Conclusions: The new risk index combining HE4, d -dimer, fibrinogen, and CA199 was the ideal combination for the screening of endometrial cancer. As a simple, rapid, nondestructive detection method, the new risk index is worth promotion in clinical practice, especially in primary medical institutions.